The pharmacokinetics and Concentration-QTc analysis of a new etomidate analog ET-26-HCl: a phase I trial in healthy Chinese subjects - He, Kun; Zhang, Wenyu; Kong, Xiangran; Li, Lize; Diao, Lei; Wen, Qing; Su, Guohai; Yang, Xiaoran; Zhao, Hongyan (Frontiers in Pharmacology, 2025)
Methoxetamine hydrochloride (ET-26-HCl) is a novel short-acting intravenous general anesthetic that retains the advantages of etomidate while minimizing its impact on adrenal cortical function. A single-center, randomized, open-label, placebo-controlled clinical trial was conducted using concentration-QTc (C-QTc) model analysis to evaluate the pharmacokinetics, clinical sedative effect, safety, and potential risk of QT interval prolongation of ET-26-HCl at doses of 0.8 mg/kg (the clinical dosage) and 2.8 mg/kg. In the 0.8 mg/kg group, the mean peak concentration (Cmax) of ET-26 was 1,510 ng/mL with upper limits of the 90% confidence interval (CI) for QTcF interval corrected by baseline and placebo (ΔΔQTcF) falling within an acceptable range, not exceeding ±10 ms (−1.543 ms to +2.788 ms). The 2.8 mg/kg group exhibited a higher Cmax value for ET-26, along with corresponding mean ΔΔQTcF values that remained below the ±10 ms threshold limit. Based on the established C-QTc model analysis, it is predicted that the upper limit of 90% CI for the mean ΔΔQTcF corresponding to ET-26 at twice the Cmax of 0.8 mg/kg is ≤ ±10 ms. The study findings in conjunction with the C-QTc model demonstrated the rapid onset and recovery properties of ET-26. Furthermore, increased exposure and dose-dependent sedative/hypnotic effects were observed, with no risk of QT prolongation for this investigational drug, thereby ensuring patient safety and minimizing potential risks in its clinical application.Clinical Trials Registration NumberClinicalTrials.gov CTR20233230.